1971
DOI: 10.1111/j.1748-1716.1971.tb04980.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Transcapillary Exchange of 24Na and 51CrEDTA. An Evaluation of Factors Influencing the Extraction of these Tracers during one Passage through an Isolated Lung Preparation

Abstract: NICOLAYSEN, G . Pulmonary transcapillary exchange of P4Na and S I C r E D T A . A n evaluation of factors influencing the extraction of these tracers during onepassage through an isolated lung preparation. Acta physiol. scand. 1971. 82. 3 9 3 4 0 5 , Experiments with the single injection indicator diffusion method have been carried out in an isolated, ventilated and plasma-perfused rabbit lung preparation. A mixture of two diffusible tracers (24Na, W r E D T A ) and one intravascular reference tracer ( 12jI-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In order to avoid vasomotion and uncontrolled variations in vascular resistance 15 mg papaverine chloride was added to the perfusate. By alternating between the two perfusion circuits, maintaining constant mean flow, the effect of switching from low to high F,oz could be studied repeatedly during the Hauge & Nicolaysen (1971) found that the lung preparation used in the present studies had normal ultrastructure without interstitial edema after several hour\ of perfusion with pulsatile plasma flow at physiological vascular pressures and normal vascular resistance.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…In order to avoid vasomotion and uncontrolled variations in vascular resistance 15 mg papaverine chloride was added to the perfusate. By alternating between the two perfusion circuits, maintaining constant mean flow, the effect of switching from low to high F,oz could be studied repeatedly during the Hauge & Nicolaysen (1971) found that the lung preparation used in the present studies had normal ultrastructure without interstitial edema after several hour\ of perfusion with pulsatile plasma flow at physiological vascular pressures and normal vascular resistance.…”
Section: Methodsmentioning
confidence: 83%
“…the transit of Evans blue through the lungs during pulsatile and non-pulsatile flow was examined. The experimental setup was identical to that described above, except that the total venous outflow from the preparation could be diverted to a rapid sampling system (Nicolaysen 1971). By this system the outflow from the lungs could be sampled in split fractions with one sample per 0.67 s. Since the total outflow could be sampled there was no recirculation.…”
Section: Methodsmentioning
confidence: 99%
“…However, the velocity of flow in pulmonary capillaries is likely to be similar to that for systemic capillaries, since although fewer in number the pulmonary capillaries have a wider diameter than systemic capillaries (Folkow & Neil, 1971). Nicolaysen (1971) found decreasing extraction of both Na' and EDTA with time in the isolated plasma-perfused rabbit lung. Both molecules showed a parallel rate of decrease.…”
Section: Extraction Valuesmentioning
confidence: 91%
“…Crone (1 963), using a similar technique, found negligible extraction of sucrose and inulin by the lungs and concluded that the indicator diffusion method was unsuitable for tissues with high perfusion rates. Nicolaysen (1971) found significant extraction of both %Na and "Cr-EDTA, which decreased rapidly with time in the isolated rabbit lung. Since he found only small differences in permeability between normal lungs and those made oedematous with EDTA, the author concluded the technique was insensitive.…”
Section: Introductionmentioning
confidence: 94%